2013
DOI: 10.2196/jmir.2443
|View full text |Cite
|
Sign up to set email alerts
|

The Personal Health Record Paradox: Health Care Professionals’ Perspectives and the Information Ecology of Personal Health Record Systems in Organizational and Clinical Settings

Abstract: BackgroundDespite significant consumer interest and anticipated benefits, overall adoption of personal health records (PHRs) remains relatively low. Understanding the consumer perspective is necessary, but insufficient by itself. Consumer PHR use also has broad implications for health care professionals and organizational delivery systems; however, these have received less attention. An exclusive focus on the PHR as a tool for consumer empowerment does not adequately take into account the social and organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
145
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(158 citation statements)
references
References 54 publications
10
145
0
3
Order By: Relevance
“…With the PHR e-mail communication so important to the participant and the productive interactions necessary for improved outcomes, focusing the PHR training on the patient-provider messaging component of the tool may be a logical first step in increasing the use and usability of these systems. 41 It was surprising to find most of the participants of this study described themselves as ''self-taught'' in using the system. Many stated they learned the system through ''trial and error.''…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…With the PHR e-mail communication so important to the participant and the productive interactions necessary for improved outcomes, focusing the PHR training on the patient-provider messaging component of the tool may be a logical first step in increasing the use and usability of these systems. 41 It was surprising to find most of the participants of this study described themselves as ''self-taught'' in using the system. Many stated they learned the system through ''trial and error.''…”
Section: Discussionmentioning
confidence: 80%
“…[42][43][44] Educating individual providers on how they can train their chronically ill adults to use PHRs for selfmanagement support and for communication may promote better adoption and use. 9,41,42 During the course of the interviews, most of the participants reported trouble with system design and navigation. Many stated they did not like to have to search in individual encounters to find specific results.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on PHRs' use and user practices has identified a number of tensions. For instance, patients and health providers may have diverging views on personal health information (Piras and Zanutto 2010) and on the distribution of duties among the patient and the provider (Nazi 2013;Turvey et al 2014). Tang and colleagues argue that from a healthcare provider's perspective, not all patient-supplied data can inform providers' decision making; this information could be Bclinically irrelevant^or become overwhelming for a healthcare provider to review (Tang et al 2006).…”
Section: The Phr Conceptmentioning
confidence: 99%
“…Despite significant interest and anticipated benefits for consumers and healthcare providers, the overall adoption of PHRs remains relatively low [7]. A study on MyHealthVet PHR system showed the authentication and secure messaging had important consequences for access, communication, patient self-report and patient/provider relationship.…”
Section: Introductionmentioning
confidence: 99%